Desenvolvimento e aplicação do software HERisk para avaliação espaço-temporal de riscos: estudo de caso do rio Monjolinho e suas águas tratadas com membranas de matriz mistas - Neris, Jordan Brizi (2023)
This project proposes to develop new software for the spatio-temporal assessment of radiological, ecological, and human health risks, in addition to new mixed matrix membranes (MMMs) based on polyethersulfone (PES) and mesoporous materials for the removal of metallic ions (Cd2+, Cr6+, Ni2+, and Pb2+) and carbamazepine (CBZ) from aqueous solutions. The new HERisk (Human, Ecological and Radiological risk) software changes the values of the residents physiological and behavioral parameters over the years, which makes it possible to assess risks to human health in a more realistic way. The software was applied utilizing data from the literature referring to a mining area in the municipality of Itagibá (Bahia, Brazil) to show its usefulness in assessing environmental and human health risks. The results indicate a high human health risk in the entire area around the mine, while the pollution indices confirmed anthropic contamination around the mining area, especially in the locations closest to waste dumps. The MMMs developed in this study were synthesized via the phase inversion method using PES and pure (MCM-41) or functionalized (NH2-MCM-41 or SH-MCM-41) mesoporous materials. The mesomaterials and MMMs were characterized and the metal ions and CBZ quantification was performed by ICP OES and UPLC, respectively. The preliminary adsorption study showed that PES/SH-MCM-41-based MMMs present the highest potential for CBZ adsorption, while MMMs did not show significant differences for metal ions adsorption. The multivariate design (Doehlert matrix) results indicated that three independent variables (contact time, initial concentration, and the amount of SH-MCM-41 incorporated in the polymer matrix) significantly influence the MMMs adsorption capacity for CBZ, while only one factor (initial concentration) affected the removal of ions by MMMs. The application of the HERisk software and the most suitable MMM for removing toxic chemical species (TCS) was carried out in surface water samples collected in the Monjolinho river basin (São Carlos, SP). The results indicated the presence of natural and anthropogenic enrichment sources along the basin. The pollution indices calculated before the mitigation tests show a high contamination degree of the Monjolinho river basin, mainly at the sampling points located after the wastewater treatment plant (WWTP) of São Carlos. Despite this, there are no risks to the fauna and flora of the area. After the mitigation process using the MMM synthetized with 7% of NH2-MCM-41 (MMM-N7), the ecological risk assessment indicated no pollution of the water samples. For these reasons, the HERisk software and the MMM-N7 show a high potential for a more realistic and faster characterization of risks and water systems mitigation contaminated by TCS.